(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Engineering site investigation is crucial to characterize the subsurface soil of proposed construction sites. Application of 2D Electrical Resistivity Imaging ERI technique pro- vides useful information about the subsurface geology and the condition along profiles. In this paper, numerical and field studies using 2D ERI technique were adopted for engineer- ing site investigation purposes. The Wenner-Schlumberger array was implemented along three parallel profiles at the construction site of Diyala University, northeast of Baghdad city, to detect buried utilities (pipes) left over in the area. A synthetic resistivity model of a buried pipe was designed to discuss and validate the field results. The 2D ERI sections of the model resolve clearly the buried structure, even with 5% noise level. Interpretation of the field data showed that 2D ERI technique was effective in delineating the buried pipes. The vertical and horizontal sensitivity of the Wenner-Schlumberger array for sub- surface resistivity variations made it possible to determine the position and geometry of the buried structures. The current work demonstrates the usefulness of the ERI technique as a complementary tool for engineering site investigation .